Implementation of Digital-Based Authentic Assessment in Assessing Student Competencies - Rieneke Ryke Kalalo; Yossie Ulfa Nuzalifa; K. Rapiandi Isak Merang; Azhariah Rachman; Fredik Edison Nope (CV. Edujavare Publishing, 2026)
The rapid development of information and communication technology has brought significant changes to various aspects of life, including education. This study aims to analyze the implementation of digital-based authentic assessment in assessing student competencies and identify factors that influence its success. The approach used was qualitative with a descriptive design. The research subjects included teachers and students who had implemented digital-based assessment in the learning process. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used an interactive model that included data reduction, data presentation, and drawing conclusions. Data validity was tested through triangulation of sources and methods. The results showed that digital-based authentic assessment was able to provide a more comprehensive picture of student competencies, covering cognitive, affective, and psychomotor aspects. The implementation of this assessment encouraged increased student engagement, creativity, and critical and collaborative thinking skills. In addition, the use of digital technology facilitated the management of assessment data, the provision of feedback, and increased the transparency of the evaluation process. However, several obstacles to its implementation existed, such as limited infrastructure, low digital literacy among some teachers and students, and the potential for academic dishonesty.